Metode Tafsir al-Qur'an untuk Anak Didik: Studi Buku Tafsir al-Qur'an Karya Afif Muhammad - Adib, Shohibul (Al-Riwayah : Jurnal Kependidikan, 2018)
The exegeticalmethods of the Quran has been aimed more and consumed by adults both from students, students, lecturers, and intellectuals, rather than to children. But actually, the case of adults is clearly different from the nature of children who have a tendency to play. How to present a exegeticalmethod of the Quran that can be consumed by children is a developmental idea in the scientificexegesis of the Quran in general and particularlyin the Islamic Religious Education (PAI), especially in the study of the exegesis of the Quran. Therefore, Tafsir Qur'an untuk Anakanak (The Exegesis of the Quran for Children) by Afif Muhammad comes to respond to the problem when it is now very rarely the literature that deals with the interpretation for children today. Therefore, this paper will discuss how the exegeticalmethod offered by Afif Muhammad in his work, and most importantly is, how to present the characteristics of the exegesis of the Holy Quran that is ideal for children in the perspective of Islamic Religious Education (PAI).The result of this research reveals that the ijmāli method with dialogical language in Tafsir Qur'an untuk Anak-anak can be used as a solution to improve the lecture method in PAI so as to create dynamic and effective interrelations between educators and learners in the learning process. The comic method in the Tafsir Qur'an untuk Anak-anak is a prominent characteristic of the study of the Qur'an for children so that it can be utilized by educators in the process of teaching and learning in the classroom, and the scholars who are concerned about the world education of children.